Moral Development Strategies in Shaping Adolescent Character Through the Qur'an - Muhsin, Muhsin; Warisno, Andi; Ansori, Afif; Andari, An An (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
The purpose of the study was to determine the strategies of adolescent moral formation by collecting various research results in journal articles. This is intended for the younger generation to improve themselves and prepare them to build the nation in the future. This research is a systematic review through a review of journal articles about various ways of forming adolescent morals in obtaining Islamic adolescent characters. Article searches in Indonesian & English are accessed using the internet from the Google Scholar database, ScienceDirect, and many other article search engines. From this search, the keywords are moral formation strategies, youth, and the Qur'an. Data analysis using content analysis. The results of this review indicate that the moral formation of adolescents is very important in shaping the personality of adolescents and is expected to be able to build a nation with moral values that are guided by the Qur'an. Not only that, teenagers are also equipped with moral values to carry out their future lives.